Hubungan Smartphone Addition terhadap Tingkat Konsentrasi Belajar pada Remaja SMP Negeri 11 Kota Jambi - Pini Sepriani; Kamariyah Kamariyah; Riska Amalya Nasution; Yuliana Yuliana; Luri Mekeama (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2026)
Excessive smartphone use among adolescents, especially students, can develop into smartphone addiction and potentially disrupt learning concentration. At SMP Negeri 11 Jambi City, most students use smartphones for long periods for entertainment and social media until late at night, which leads to drowsiness and reduced focus during lessons. This study employed a quantitative method with a cross-sectional design. The population consisted of all seventh-grade students at SMP Negeri 11 Jambi City, totaling 352 students, with a sample of 175 respondents selected through stratified proportionate random sampling. Data were collected using the Smartphone Addiction Scale–Short Version (SAS-SV) questionnaire and a learning concentration questionnaire. Data analysis was conducted using univariate and bivariate methods with Kendall’s tau-b test. The results showed that 84% of respondents experienced smartphone addiction, while 61.7% had a good level of learning concentration. Kendall’s tau-b test indicated a significant relationship between smartphone addiction and learning concentration (p-value = 0.000; r = 0.243), showing a weak association. Higher levels of smartphone addiction were linked to decreased learning concentration. Therefore, active involvement from schools and parents is needed to guide adolescents in managing stress and boredom positively.